PIM-funded research in Haryana, India, informed the design of innovative picture-based insurance products, reducing insurance premiums by approximately 50%. - CGIAR Research Program on Policies, Institutions, and Markets (2017)
A formative evaluation of Picture-Based Insurance (PBI) conducted in 2016-2017 provided evidence to insurance and advisory service providers that PBI is a feasible and economically viable tool to provide affordable crop insurance to poor smallholder farmers, and reducing basis risk relative to weather index-based insurance. The findings led HDFC to offer PBI during the next season at a significantly lower premium. Further, this new product was leveraged by CABI and BKC WeatherSys to offer complementary advisory services around risk management.